Potential Hazards and Associated Causal Factors in the Occupational Environment of Palm Oil Workers - Istisya, Afifah Salsabilla; Denny, Hanifa Maher; Setyaningsih, Yuliani (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction:Palm oil workers are exposed to numerous hazards in the work environment associated with accidents and occupational diseases. Work-related accidents are typically influenced by a combination of internal and external factors. Therefore, this study aimed to analyze the potential hazards and influencing factors affecting the safety of workers in palm oil gardens. Method: PRISMA guidelines with Boolean operators were used alongside specified keywords "Safety Work ” OR " Health Work " AND " Hazard" AND " Palm Oil ” AND " Worker.” The inclusion criteria for the review included articles published from 2019 to 2023. Results: The results showed that factors psychologically influencing work accidents among palm oil workers included length of service, knowledge, attitudes, as well as the use of PPE, and overtime system. In terms of potential ergonomic hazards, the influencing factors identified were work posture, workload, and repetitive movements while working. From the aspect of potential biological and chemical hazards, the use of PPE when spraying pesticides and cleanliness were found to play a crucial role in the prevention of infection and exposure to chemical materials. Conclusion: Based on the results from several studies, smallholder palm oil workers have the potential to experience occupational accidents and diseases in the form of physical, biological, chemical, and ergonomic hazards. However, by adopting a comprehensive approach to mitigating these complex hazards, stakeholders can create a safer and more sustainable work environment.